Impact of impact factor, IF: Pros and cons in research, writing, and publication - N Shah, Jay; Man Singh Pradhan, Nabees; Shrestha, Ashis; Prasad Deo, Gopendra (Journal of Chitwan Medical College, 2024)
Dissemination of scientific research work by publishing in an appropriate journal is necessary in science. The journal’s characteristics, quality and prestige are important factors. There is no single straightforward and clear measurement for the quality and ranking of journals. Beyond the basic requirement of peer review, a regular publication by a robust editorial board and its reputable members should be considered. The quality and prestige of journals depend on their characteristics and include the indexing of a journal, i.e. on which databases a journal is listed, i.e. indexed. Among many indexing platforms, journal impact factor or simply impact factor (IF) for journals listed in Web of Science provides a ranking for its journals, i.e. Science Citation Index journals. The IF is a citation-based journal metric that has become synonymous for journal prestige. The IF is released yearly by the Journal Citation Report and is considered the most influential for quality and prestige by authors, journal editors, publishers, and academia despite the limitations in the calculation. The IF in the current year is calculated by the total number of papers published in a journal in the previous two years divided by the total number of citations to the published articles in those two years. To overcome the possible limitation of IF, the know-how of other metrics like SCImago, cite-score, h-index and others should be considered. Keywords: Cite-Score, H-Index, Impact Factor, Research Writing Publication, Science Citation Index, Scimago Author Biographies Jay N Shah, Chitwan Medical College Prof, Head of Department of Surgery, Editor in Chief of Journal of Chitwan Medical College, Nepal; ex- Editor in Chief of Journal of Patan Academy of Health Sciences and Journal of Society of Surgeons of Nepal, ex-president of Nepal Association of Medical Editors Nabees Man Singh Pradhan, Patan Academy of Health Sciences Prof, Head of Department of Orthopedic and Trauma, Editor in Chief of Journal of Patan Academy of Health Sciences, Nepal Ashis Shrestha, Patan Academy of Health Sciences Asssoc Prof, Chief Editor Journal of Nepal Medical Association, Nepal, ex-Editor in Chief of Journal of General Practice and Emergency Medicine of Nepal Gopendra Prasad Deo, Chitwan Medical College Prof, Anaesthesiology and Critical Care, ex-Editor in Chief of Journal of Chitwan Medical College, Nepal